Burnout, psychological wellbeing, and musculoskeletal complaints in UK GPs: an observational study - Gregory JH Biddle; Nicholas Thomas; Charlotte L Edwardson; Stacy A Clemes; Amanda J Daley (BJGP Open, 2023)
Background: Healthcare systems are under unprecedented pressure. GPs are crucial to the health of the population, yet their own health and wellbeing is often overlooked. Aim: To investigate feelings of burnout, psychological wellbeing, and musculoskeletal complaints in GPs across the UK and to examine whether these health outcomes vary according to the time GPs spent sitting, their participation in physical activity each day, and the time spent working per day or week. Design & setting: Observational study involving GPs located across the UK. Method: An online survey was emailed to working members of the Royal College of General Practitioners and shared on social media between October and December 2020. The survey included questions on burnout, psychological wellbeing, musculoskeletal complaints, sitting time, physical activity, and time spent working. Mean differences were examined for burnout, psychological wellbeing, and musculoskeletal complaints. Results: Data from 406 GPs showed a high level of burnout (35.5%) and musculoskeletal complaints (neck, shoulder and back: 81.8%; arms: 28.3%; and legs: 49.8%). Psychological wellbeing was low in 22.9% of GPs. Burnout was lower in GPs who met current physical activity guidelines, while psychological wellbeing was higher in those with >2 breaks in sitting per hour. Musculoskeletal complaints were higher in those spending >50% of sitting time in prolonged bouts (≥30 minutes). Conclusion: A high proportion of GPs reported experiencing burnout and musculoskeletal complaints, but these health concerns were less evident in GPs who spent less time in prolonged sitting, took more breaks in sitting, and who were more physically active.